Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis among women with genitourinary infection and pregnancy-related complications in Tehran: A cross-sectional study. (July 2020) - Rajabpour, Mohammadreza; Emamie, Amir Darb; Pourmand, Mohammad Reza; Goodarzi, Narjes Noori; Asbagh, Firouzeh Akbari; Whiley, David M
The present study investigates the prevalence of Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), and Trichomonas vaginalis (TV) among women with genitourinary infection and pregnancy-related complications in Tehran. It also evaluates the demographic information, symptoms, and sequelae. Endocervical samples were obtained over a period of eight months from 360 women including 180 symptomatic patients and 180 patients with pregnancy-related complications and infertility. CT, NG, and TV were detected in 10.8%, 6.9%, and 8.3% of all patients, respectively. The prevalence of CT, NG, and TV among women in the symptomatic group was 11.1%, 7.2%, and 13.3%, respectively, and among women with pregnancy-related complications and infertility was 10.6%, 6.7%, and 3.3%, respectively. Associations between chlamydia and ectopic pregnancy ( p  =   0.001), and infertility ( p  <   0.001) were observed. Abortion ( p  =   0.008), infertility ( p  =   0.005), and ectopic pregnancy ( p  <   0.001) were associated with gonorrhea. Abnormal vaginal discharge ( p  =   0.02) and vulvar itching ( p  =   0.02) were associated with trichomoniasis. Overall, the prevalence rates of CT, NG, and TV were high in these patient groups. These high prevalences suggest that screening programs are required to reduce the burden of these sexually transmitted infections and their effects on genitourinary symptoms, pregnancy-related complications, and infertility.